COMPARATIVE ANALYSIS OF DRUG EFFICACY IN THE TREATMENT FOR COVID-19 SEVERE FORMS, BASED ON ATTRIBUTE-BASED STATISTIC METHODS AND ANALYSIS OF DRUG INTERACTIONS - O. V. Zhukova; I. N. Kagramanyan; A. L. Khokhlov (Фармация и фармакология (Пятигорск), 2021)
Severe and critical forms of COVID-19 are beset by the development of “a cytokine storm”, which is characterized by an increased secretion of proinflammatory cytokines. Therefore, one of the leading strategies for treating patients with severe forms of COVID-19 is the reduction of concentration of proinflammatory cytokines and leveling out their effect on the patient. Among the drugs aimed at reducing the concentration of proinflammatory cytokines, IL-6 inhibitors, IL-1 inhibitors, JAK inhibitors and systemic glucocorticosteroids have been found useful in COVID-19. All of these drugs are currently prescribed off-label.The aim of the work is a comparative analysis of the data from the literature sources in the PubMed system, devoted to the clinical efficacy and safety of IL-6, IL-1, JAK inhibitors and systemic glucocorticosteroids in the treatment for severe forms of COVID-19.Materials and methods. In the treatment for severe forms of COVID-19, materials for the comparative analysis were the data from the literature sources in the PubMed system, on the studies devoted to the use of the systemic glucocorticosteroid dexamethasone, IL-6 inhibitor tocilizumab, IL-1 inhibitor anakinra, and JAK inhibitor ruxolitinib. The analysis was performed by statistical evaluation of the drugs effect within the 28-day survival rate among the patients with severe COVID-19. Attributive statistics was used as a statistical tool. The safety of the drug use was assessed by analyzing potential drug interactions. The information about potential drug interactions, was obtained from a specialized website – Drugs.com. Knowmore. Besure (https://www.drugs.com/interaction/list/).Results. As a result of the analysis, it has been established that tocilizumab has the highest efficacy rates. In this respect, it is followed by dexamethasone. The attributive efficacy rates and 95% confidence interval values for the both drugs were statistically significant. The indices of relative and population attributive kinds of efficacy, were also higher for tocilizumab, but a 95% confidence interval of these indices, get into the range of statistically insignificant values, requiring additional evidence of their efficacy. According to the data obtained, tocilizumab efficacy is higher than that of the other drugs compared: NNT (dexamethasone) – 32; NNT (tocilizumab) – 4, NNT (ruxolitinib) – 7; NNT (anakinra) – 35.Conclusion. The choice of a drug should be based on the patient’s condition, comorbidities, and medications used in therapy to minimize the risk of undesirable drug interactions. Against the background of the lowest efficacy among the compared drugs, a high efficacy for the patients with concomitant hepatobiliary disorders and DIC syndrome, has been established for the inhibitor IL-1 anakinra, which makes it the drug of choice among the patients with these diseases and under these conditions in the development of “a cytokine storm”.